Somatostatin receptor subtype 2A immunohistochemistry using a new monoclonal antibody selects tumors suitable for in vivo somatostatin receptor targeting - Körner, Meike; Waser, Beatrice; Schonbrunn, Agnes; Perren, Aurel; Reubi, Jean Claude (The American journal of surgical pathology, 2012)
High overexpression of somatostatin receptors in neuroendocrine tumors allows imaging and radiotherapy with radiolabeled somatostatin analogues. To ascertain whether a tumor is suitable for in vivo somatostatin receptor targeting, its somatostatin receptor expression has to be determined. There are specific indications for use of immunohistochemistry for the somatostatin receptor subtype 2A, but this has up to now been limited by the lack of an adequate reliable antibody. The aim of this study was to correlate immunohistochemistry using the new monoclonal anti-somatostatin receptor subtype 2A antibody UMB-1 with the gold standard in vitro method quantifying somatostatin receptor levels in tumor tissues. A UMB-1 immunohistochemistry protocol was developed, and tumoral UMB-1 staining levels were compared with somatostatin receptor binding site levels quantified with in vitro I-[Tyr]-octreotide autoradiography in 89 tumors. This allowed defining an immunohistochemical staining threshold permitting to distinguish tumors with somatostatin receptor levels high enough for clinical applications from those with low receptor expression. The presence of >10% positive tumor cells correctly predicted high receptor levels in 95% of cases. In contrast, absence of UMB-1 staining truly reflected low or undetectable somatostatin receptor expression in 96% of tumors. If 1% to 10% of tumor cells were stained, a weak staining intensity was suggestive of low somatostatin receptor levels. This study allows for the first time a reliable recommendation for eligibility of an individual patient for in vivo somatostatin receptor targeting based on somatostatin receptor immunohistochemistry. Under optimal methodological conditions, UMB-1 immunohistochemistry may be equivalent to in vitro receptor autoradiography.